Values Education in Early Childhood Settings Concepts, Approaches and Practices (International Perspectives on Early Childhood Education and Development,, 2018)
This book is about values education in early years settings and discusses theory and concepts, as well as methodological and empirical perspectives. It explores issues such as the kinds of values that are communicated between educators and children and the kind of future citizens we foster in early childhood settings. It illustrates by way of cases involving many participants, including children, educators, and researchers, who have their roots in diverse contexts, and reside in different parts of the world, including Australia, Denmark, Finland, Iceland, Norway, Slovenia, and Sweden. The book carefully considers the contextualized character of the cases presented, yet argues that the questions, theories, and methodologies emphasized do inform the international debate in manifold ways. Communication of values in a broad and diverse sense is central in any pedagogy, especially for the youngest children in the educational system. Still, values education has been neglected as a research field, in education in general and particularly in the early years. This book addresses this lack of knowledge by scrutinizing various questions about values education in ECEC settings. .